2022
DOI: 10.1080/23335432.2022.2142159
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical testing of different fixation techniques for intraoperative proximal femur fractures: a technical note

Abstract: Intraoperative proximal femoral fractures (IPFF) represent a rare but challenging complication of total hip arthroplasties. They usually occur as a longitudinal split. This pilot trial aimed to compare the biomechanical primary stability of different fixation techniques for IPFF. Standardised longitudinal medial split fractures of the proximal femur (type II, Modified Mallory Classification) were created in artificial osteoporotic and non-osteoporotic composite femora after implantation of a cementless femoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…In terms of treatment, cerclage wiring or cabling was recommended for type 1 and type 2 fractures, while fracture fixation with or without use of a long stem for type 3 fractures 10,11 . A recent biomechanical study demonstrated that there were no significant difference in the primary stability according to the fixation modalities (cerclage band, cerclage wiring, and lag screws) in Mallory type 2 femurs 27 . Therefore, for stable fixation, identification of the location and extent of fracture seems to be more imperative regardless of the fixation device when appropriately treated.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of treatment, cerclage wiring or cabling was recommended for type 1 and type 2 fractures, while fracture fixation with or without use of a long stem for type 3 fractures 10,11 . A recent biomechanical study demonstrated that there were no significant difference in the primary stability according to the fixation modalities (cerclage band, cerclage wiring, and lag screws) in Mallory type 2 femurs 27 . Therefore, for stable fixation, identification of the location and extent of fracture seems to be more imperative regardless of the fixation device when appropriately treated.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of treatment, cerclage wiring or cabling was recommended for type 1 and type 2 fractures, while fracture fixation with or without use of a long stem for type 3 fractures 10,11 . A recent biomechanical study demonstrated that there were no significant difference in the primary stability according to the fixation modalities (cerclage band, cerclage wiring, and lag screws) in Mallory type 2 femurs 27 . Therefore, for stable fixation, identification of the location and extent of fracture seems to be more imperative regardless of the fixation device when appropriately treated.…”
Section: Discussionmentioning
confidence: 99%
“…A distance of 70 mm between embedding and templated stem tip position was chosen independent from implant length and size to achieve a comparable bending situation [ 42 ]. The stem length varies between the stem designs as well as between the stem sizes.…”
Section: Discussionmentioning
confidence: 99%